Causes and Temporal Patterns of 30‐Day Readmission Among Older Adults Hospitalized With Heart Failure With Preserved or Reduced Ejection Fraction. Issue 9 (12 September 0207) - Goyal, Parag; Loop, Matthew; Chen, Ligong; Brown, Todd M.; Durant, Raegan W.; Safford, Monika M.; Levitan, Emily B.
Abstract : Background: It is unknown whether causes and temporal patterns of 30‐day readmission vary between heart failure (HF) with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF). We sought to address this question by examining a 5% national sample of Medicare beneficiaries. Methods and Results: We included individuals who experienced a hospitalization for HFpEF or HFrEF between 2007 and 2013. We identified causes of 30‐day readmission based on primary discharge diagnosis and further classified causes of readmission as HF‐related, non–HF cardiovascular‐related, and non–cardiovascular‐related. We calculated the cumulative incidence of these classifications for HFpEF and HFrEF in a competing risks model and calculated subdistribution hazard ratios of these classifications by comparing those with HFpEF and those with HFrEF. Among 60 640 Medicare beneficiaries, we identified 13 785 unique older adults hospitalized with HFpEF and 15 205 who were hospitalized with HFrEF. Noncardiovascular diagnoses represented the most common causes of 30‐day readmission (HFpEF: 59%; HFrEF: 47%), a pattern that was observed for each week of the 30‐day study period for both HFpEF and HFrEF participants. In comparing readmission diagnoses in an adjusted model, non–cardiovascular‐related diagnoses were more common and HF‐related diagnoses were less common in HFpEF participants. Conclusions: Non–cardiovascular‐related diagnoses represented the most common causes of 30‐day readmission following HF hospitalization for each week of the 30‐day postdischarge period. HF diagnoses were less common among those with HFpEF compared with HFrEF. Future interventions aimed at reducing 30‐day readmissions following an HF hospitalization would benefit from an increased focus on noncardiovascular comorbidity and interventions that target HFpEF and HFrEF separately.